EVALUASI PENERAPAN PERATURAN PEMERINTAH NO.71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL PADA LAPORAN OPERASIONAL BPKAD KABUPATEN KONAWE - Dharmawati, Tuti; Intihanah, Intihanah; Trisilia, Putri Harum Sari (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACTThis study aims to determine the implementation of operational reports BPKAD Konawe District has in accordance with Government Regulation Number 71 of 2010 on Accounting Standards Government-Based Accrual on been applied properly.This research was conducted at BPKAD Kabupaten Konawe. Data in this research are primary data and secondary data. Primary data obtained from interview and secondary data in this research is Operational Report for fiscal year 2016. Data analysis method used is descriptive analysis method is a method that describes in advance about the recording, recognition, and reporting of burden .The results of this study indicate that BPKAD Kabupaten Konawe in preparing operational reports in accordance with Government Regulation Number 71 of 2010 on Accounting Standards Government-Based Accrual. This can be seen from the results of recording, recognition, and reporting of the LO-load on the Regional Management and Asset of Konawe Regency which has been in accordance with Government Regulation No. 71 of 2010 on Accounting Standards Based on Accrual Government.Â Keywords: Accrual Base, Operational Report.Â